OPTIMIZING EMPLOYEE PERFORMANCE IN ISLAMIC EDUCATIONAL INSTITUTIONS: THE INTERPLAY OF LEADERSHIP, MOTIVATION, AND WORK DISCIPLINE - Afandi, Ahmad; Rahmayati, Rahmayati; Rowiyah, Rowiyah (Proceeding International Seminar of Islamic Studies, 2025)
This study examines the relationship between early childhood English language acquisition and Islamic education, emphasizing the benefits and difficulties present in this dynamic learning environment. The need for English language proficiency among young students in Islamic educational settings has significantly expanded as a result of growing globalization. According to this study, cultural views, disparities in teacher ability, and a lack of resources are some of the main obstacles that can prevent effective English language instruction. However, it also draws attention to significant chances to incorporate Islamic principles into English language instruction strategies in order to improve students' involvement and contextual awareness. This study intends to provide information on efficient teaching techniques that are in line with both Islamic teachings and contemporary language learning techniques by using qualitative approaches such as interviews and classroom observations. The findings of the study indicate that early childhood students enrolled in Islamic education can greatly increase their English proficiency with a well-rounded approach that honors cultural context while implementing cutting-edge teaching techniques. This study offers useful suggestions for educators and legislators who want to establish more inclusive and productive learning settings, as well as contributing to the current conversation on multilingual education.